Calcium Signaling Mechanisms Across Kingdoms - Luan, Sheng; Wang, Chao (Annual review of cell and developmental biology, 2021)
Calcium (Ca ) is a unique mineral that serves as both a nutrient and a signal in all eukaryotes. To maintain Ca homeostasis for both nutrition and signaling purposes, the tool kit for Ca transport has expanded across kingdoms of eukaryotes to encode specific Ca signals referred to as Ca signatures. In parallel, a large array of Ca -binding proteins has evolved as specific sensors to decode Ca signatures. By comparing these coding and decoding mechanisms in fungi, animals, and plants, both unified and divergent themes have emerged, and the underlying complexity will challenge researchers for years to come. Considering the scale and breadth of the subject, instead of a literature survey, in this review we focus on a conceptual framework that aims to introduce readers to the principles and mechanisms of Ca signaling. We finish with several examples of Ca -signaling pathways, including polarized cell growth, immunity and symbiosis, and systemic signaling, to piece together specific coding and decoding mechanisms in plants versus animals.